Menyentuh Mushaf Tanpa Wudu dalam Perspektif Mazhab SyÄfiâ€™Ä« dan Hanbali - Saifullah Bin Anshor; Sartini Lambajo; Dewi Indriani; Izzati, Rizqa (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2021)
This study aimed to find out how the law of touching Mushaf of the Qur'an for people who are in hadas according to the SyÄfi'Ä« and Hanbali schools. The type of study was descriptive qualitative research that focuses on retrieving data sources from library research using a normative juridical approach. The results showed that the sects of SyÄfi'Ä« and Hanbali both viewed the prohibition of touching Mushaf of the Qur'an without wudu for the person in hadas. As for the law of touching or carrying a mushaf wrapping sheath (which has a hanger) or a box in which there is a Mushaf of the Qur'an, the sects of SyÄfi'Ä« and Hanbali differ. The SyÄfi'Ä« sect thinks it is haram because it is made for mushaf and converted to it like a mushaf cover skin. The Hanbali sect argues that it is permissible not to touch the mushaf because what is forbidden is touching, while carrying does not mean touching. This difference arises because of differences in views on the basis of qiyas in the source of the law of its sect.